Optimizing The Panic of Football Players - Gapparov Zaxid Gapparovich; Ishtayev Javlon Mavlonboyevich; Ishtayeva Rano Abdusidiq qizi (Genius Publishing Group, 2023)
In this article, the author highlights the scientific and methodological aspects of the psychological training of football players in the the Ch.D. Spielberger reactive anxiety scale on an experimental basis.
Keywords: football player; state of anxiety; activity